Immersive technologies and AI generate novel challenges to human subjects’ protections protocols - Scott, Julia A.; Bagade, Aryan; Choudhary, Bhanujeet (Frontiers in Virtual Reality, 2026)
IntroductionImmersive technologies enabled by AI present latent risks to human subjects’ protections in research settings. Standard methods of ensuring confidentiality, data management, and safety do not fully encompass the scope of data types, data flow, and user experience. A comprehensive take on risk assessment and mitigation strategy is warranted.Methods100 research compliance officers analyzed three case studies (Biodata, Haptics, Motion Tracking) in a structured sequence (Open Inquiry, Technical Analysis, Risk Assessment, Mitigation Strategies). The text responses to the questions were thematically coded and summarized in the context of the review criteria (Data Management, Informed Consent, Safety, and Training).ResultsBiodata case study presented challenges in psychological safety that could be mitigated with improved withdrawal procedures. Haptics introduced novel physical safety concerns with direct brain stimulation, which called for thorough training of study personnel. Motion-tracking exposed the difficulty of anonymization, which may require enhanced data security measures in the data management plan.DiscussionThe technical depth of knowledge impacted compliance officers’ analysis of the case studies. Yet when informed, the adapted application of human subjects’ protections policies could capture much of the latent risk. The proposed review criteria establish a structure to assess research practices with immersive technology.